Stem cells and neurodegenerative diseases - Lescaudron, Laurent; Rossignol, Julien; Dunbar, Gary L. (Boca Raton : CRC Press/Taylor & Francis, 2014)
'This book explores the potential of stem cells for ameliorating the quality of life of patients with neurological and neurodegenerative diseases. It discusses results of pre-clinical investigations and case studies on the effects of stem cell transplantation on cell death, as well as to promote/stimulate neuroprotection after brain and spinal cord injury through trophic support, cell replacement and remyelination. The book covers the maintenance of the balance between stem cells and their progenitors within their niche, both under normal and degenerative processes and with ischemic stroke, multiple sclerosis, and brain tumor'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Neurodegenerative Diseases -- therapy; Stem Cells